Preparation method of injectable hydrogel dressing containing self-assembled activated nanozymes, product and application thereof
By using self-assembled injectable hydrogel dressings with activated nanoenzymes on diabetic wounds, the problem that the existing technology cannot effectively alleviate the high sugar microenvironment of diabetic wounds, and the effective healing and antibacterial effects of the wounds are achieved.
Patent Information
- Application Number
- CN202311756656.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Existing hydrogel dressings cannot effectively alleviate the negative impact of high-sugar microenvironment on the healing process on diabetic wounds.
Using self-assembled injectable hydrogel dressings to form composite hydrogel materials through borate ester bonds and Schiff alkali bonds, it contains glucose oxidase and copper selenide nanoenzymes, which can consume excessive glucose and produce reactive oxygen species at low pH environments, kill bacteria and promote wound healing.
It has achieved the relief of the high-sugar microenvironment on the diabetic wound, promoted healing, and has excellent antibacterial properties and biocompatibility.
Smart Images

Figure CN117919486B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical dressings, and specifically relates to a preparation method of an injectable hydrogel containing self-assembled activated nanozymes, and a product and application thereof. Background Art
[0002] Diabetes is one of the world's public health problems, and it is expected to affect about 10% of the world's population by 2030. Diabetic ulcers, as a common complication, have gradually become the main type of chronic and difficult-to-heal wounds in clinical practice, seriously threatening the life and health of patients. Effective revascularization has been proven to be one of the strategies to promote diabetic wound healing and functional recovery, but the local hyperglycemic environment of diabetic wounds usually induces a large accumulation of advanced glycation end products (AGEs), promotes bacterial infection, greatly inhibits the cell activity of fibroblasts and endothelial cells, such as cell migration and proliferation, and inhibits the function of immune cells. Vascular lesions at the wound site caused by hyperglycemia reduce the supply of oxygen, nutrients and growth factors, further hindering wound healing. Therefore, alleviating the high-sugar microenvironment should be conducive to timely revascularization and accelerate the healing process of diabetic wounds.
[0003] Hydrogel dressings formed by cross-linking through physical or chemical bonds can not only be used as delivery platforms for antibacterial drugs, cytokines, nanomaterials, and therapeutic stem cells, but also can release active components on demand through microenvironment responsiveness, realize intelligent regulation of the local microenvironment of the tissue, and create suitable conditions for the repair of diabetic wounds. For example, the Chinese patent with publication number CN117085170A discloses a method for preparing an injectable antibacterial hydrogel that promotes the healing of diabetic infected wounds: copper-tannic acid nanosheets CuTA, borax and photoinitiator are dissolved in deionized water, and methacrylated gelatin GelMA is added to dissolve to obtain a first solution; quaternary ammonium salt guar gum CG is dispersed in deionized water to obtain a second solution; the first solution is mixed with the second solution in a stirring state, and after mixing, light curing and cross-linking are performed to form an injectable antibacterial hydrogel. However, the hydrogel cannot improve the negative impact of the high sugar microenvironment on the wound repair process.
[0004] Therefore, how to provide a hydrogel dressing that is more effective in alleviating the high-sugar microenvironment of diabetic wounds is currently a research hotspot in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an injectable hydrogel dressing containing self-assembled activated nanozymes. A composite hydrogel material is formed by borate bonds and Schiff base bonds. The prepared hydrogel dressing has self-healing properties, weak acid and oxidative environment responsive release properties, glucose oxidase and copper selenide nanozymes triggering a cascade reaction to consume glucose, excellent antibacterial properties and excellent biocompatibility, and can be used to prepare dressings that promote healing of diabetic infected wounds.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A preparation method of an injectable hydrogel dressing containing self-assembled activated nanozymes comprises the following steps:
[0008] (1) Dissolve oxidized hyaluronic acid (OHA) and borax in water, add copper selenide nanozyme Cu 2-x Se and glucose oxidase GOx to obtain a first solution; wherein Cu 2-x x in Se is 0 or 1;
[0009] (2) dissolving gelatin and borax in water to obtain a second solution;
[0010] (3) Mixing the second solution into the first solution in a stirring state, and stirring and mixing to form an injectable hydrogel dressing containing self-assembled activated nanozymes.
[0011] In step (1), Cu 2-x The concentration of Se is 0.1-5 mg mL -1 , GOx concentration was 1-30 μg mL -1 , the concentration of OHA is 2-10% w / v, and the concentration of borax is 0.01-0.1M.
[0012] The preparation method of the oxidized hyaluronic acid (OHA) comprises: dissolving sodium hyaluronate in water, adding sodium periodate and reacting at room temperature to obtain the oxidized hyaluronic acid (OHA).
[0013] The molecular weight of the oxidized hyaluronic acid OHA is 8000-12000Da.
[0014] Furthermore, the preparation method of the hyaluronic acid OHA comprises:
[0015] 2 g of sodium hyaluronate (HA, Mw = 150-250 kDa) powder was fully dissolved in 200 mL of deionized water, followed by the addition of 1 g of sodium periodate solid. The mixture was stirred at room temperature in the dark for 24 hours, and 2 mL of ethylene glycol was added to terminate the reaction. The resulting solution was dialyzed against water for 5 days using a dialysis bag with a molecular weight cutoff of 8000-12000 Da, filtered, and freeze-dried for later use to obtain oxidized hyaluronic acid (OHA).
[0016] The copper selenide nanozyme Cu 2-x The preparation method of Se comprises: dissolving copper chloride dihydrate and bovine serum albumin in water, adding sodium hydroxide to prepare solution A; dissolving selenium powder and sodium borohydride in water to obtain solution B; adding solution B to solution A to react and obtain copper selenide nanozyme Cu 2-x Se.
[0017] Furthermore, the copper selenide nanozyme Cu 2-x The preparation method of Se comprises:
[0018] 186 mg of copper chloride dihydrate (CuCl2·2H2O) and 1 g of bovine serum albumin (BSA) were fully dissolved in 20 mL of deionized water, and 3.5 mL of 1 M sodium hydroxide solution (NaOH) was added to prepare solution A. 40 mg of selenium powder (Se) and 60 mg of sodium borohydride (NaBH4) were dissolved in 2 mL of deionized water to obtain solution B. After the solid in solution B was fully reacted and dissolved, solution B was added to solution A. The resulting brown mixed solution was stirred at 90°C for 1 hour, dialyzed against water in a dialysis bag (MWCO100 kDa) for 5 days, and freeze-dried for use to obtain copper selenide nanozyme (Cu 2-x Se).
[0019] In step (2), the concentration of gelatin in the second solution is 5-30% w / v; the concentration of borax is 0.01-0.1M.
[0020] Furthermore, the volume ratio of the first solution to the second solution is 1:1, and the stirring condition is 500-1000 rpm.
[0021] Furthermore, in step (3), the second solution is mixed into the mixed solution after the first solution is stirred, Cu 2-x The concentration of Se is 1-2 mg mL -1 .
[0022] The present invention also provides an injectable hydrogel dressing containing self-assembled activated nanozymes obtained according to the above preparation method.
[0023] The present invention also provides an application of the hydrogel dressing in preparing a diabetic infected wound dressing.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The hydrogel dressing prepared by this method has good injectability, self-healing and tissue adhesion. The injectability enables the hydrogel dressing to adapt to irregular wound surfaces, the adhesion can prevent the hydrogel dressing from falling off the wound surface, and the self-healing property enables the hydrogel dressing to return to its original state after being broken by external force.
[0026] 2. Oxidized hyaluronic acid can form a borate ester bond with borax through a cis-diol structure, and can also form a Schiff base bond with the amino group in gelatin through an aldehyde group. The formed dual dynamic bond cross-linking structure not only gives the hydrogel dressing more ideal mechanical properties, but also gives the hydrogel dressing the characteristics of dual responsiveness to disintegration and release of drugs in low pH and high oxidative stress microenvironments.
[0027] 3. Glucose oxidase and responsive self-assembled activated copper selenide nanozymes in hydrogel dressings can consume excess glucose in diabetic wounds to produce reactive oxygen species under low pH microenvironment conditions. While reducing glucose levels to promote wound repair, the reactive oxygen species produced can also effectively kill bacteria in infected wounds. The copper ions released by copper selenide nanozymes can not only promote the production of mature collagen, but also promote the migration and proliferation of endothelial cells.
[0028] Therefore, the present invention realizes the responsive release of glucose oxidase and acid-responsive self-assembled activated copper selenide nanozymes in low pH and high oxidative stress microenvironment through borate ester bonds and Schiff base bonds in injectable hydrogels, thereby triggering a cascade reaction, consuming excess glucose in infectious diabetic wounds, and generating a large amount of reactive oxygen species to kill bacteria. As the wound gradually heals, the pH of the tissue microenvironment increases, the self-assembled copper selenide nanozymes depolymerize, the peroxidase-like activity of the nanozymes disappears, limiting the continuous generation of reactive oxygen species, and promoting the healing of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The AMs are Cu prepared in Example 1 of the present invention. 2-x Transmission electron microscopy images of Se nanozymes under different pH conditions, element distribution images, aggregation and depolymerization properties of nanozymes triggered by pH changes, hydrated particle sizes under different pH conditions, Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray diffraction characterization, X-ray photoelectron spectroscopy characterization (Figures H and I), Cu under pH 5.5 2-x The properties of Se nanozymes catalyzing H2O2 oxidation of TMB, Cu 2-x The properties of Se nanozymes catalyzing H2O2 oxidation of TMB under different pH conditions, 2-xStability test of Se nanozymes in different environmental media (Figures L and M). Scale bars in the figures: A is 100 nm, B is 200 nm.
[0030] Figure 2 AJ are respectively the gelation schematic diagram and the self-healing property ( Figure 2 B and C), injectability ( Figure 2 D and H in the figure), oscillation frequency sweep, oscillation strain sweep, oscillation temperature sweep, and alternating step strain sweep experiments.
[0031] Figure 3 The AH are the responsive release, glucose degradation and catalytic oxidation properties of the hydrogels prepared in Example 2 and the comparative example, respectively. 2-x Scanning electron micrograph of OBG@CG hydrogel of Se nanozyme, element distribution of OBG@CG, catalytic oxidation of TMB by OBG@CG at different pH values, pH changes induced by OBG@CG in glucose solutions of different concentrations, changes in glucose solution concentrations induced by different hydrogels, release of Cu by OBG@CG in glucose solution 2-x Properties of Se nanozymes, degradation properties of different hydrogels in glucose solutions, and degradation properties of OBG@CG in glucose solutions at different pH values. Scale bars in the figure: A is 500μm, B is 100μm.
[0032] Figure 4 The rat liver hemostatic properties of the hydrogels prepared in Example 2 and the comparative example.
[0033] Figure 5 AK are the angiogenesis-promoting properties of the hydrogels prepared in Example 2 of the present invention and the comparative example, respectively. HUVECs scratch test ( Figure 5 A and D in the figure), Transwell assay ( Figure 5 B and E in the figure), promoting tube experiment ( Figure 5 C and F in Figure 5), HIF-1α and VEGF expression (Figures GK in Figure 5). Scale bars in Figures: A, B, and C are all 100 μm.
[0034] Figure 6 AF are the antibacterial properties of the hydrogels prepared in Example 2 of the present invention and the comparative example respectively: agarose plate culture ( Figure 6 AC in), bacterial scanning electron microscopy images ( Figure 6 B), bacterial live / dead stain ( Figure 6 Scale bars in the figure: D is 1 μm, E and F are 200 μm.
[0035] Figure 7AG are respectively the hydrogels prepared in Example 2 of the present invention and the comparative example in the rat diabetic infection model ( Figure 7 The therapeutic effect of A): wound healing effect ( Figure 7 B, C and F), H&E staining ( Figure 7 D) and Masson staining ( Figure 7 E), antibacterial effect ( Figure 7 Scale bars in the figure: 600 μm and 200 μm in D and E respectively. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] 186 mg of copper chloride dihydrate (CuCl2·2H2O) and 1 g of bovine serum albumin (BSA) were fully dissolved in 20 mL of deionized water, and 3.5 mL of 1 M sodium hydroxide solution (NaOH) was added to prepare solution A. 40 mg of selenium powder (Se) and 60 mg of sodium borohydride (NaBH4) were dissolved in 2 mL of deionized water to obtain solution B. After the solid in B was fully reacted and dissolved, all of solution B was added to solution A. The resulting brown mixed solution was stirred at 90°C for 1 hour, dialyzed against water in a dialysis bag (MWCO100 kDa) for 5 days, and freeze-dried for use to obtain copper selenide nanozyme (Cu 2-x Se).
[0039] like Figure 1 As shown, the preparation of Cu 2-x Se nanozymes were characterized. Figure 1 A in the figure shows Cu 2-x Transmission electron microscopy images of Se nanozymes under different pH conditions; Figure 1 B in is Cu 2-x Energy dispersive X-ray spectroscopy (EDX) characterization of the distribution of different elements in Se nanozymes showed that Cu, Se, and N elements were evenly distributed in the nanozymes; Figure 1 C in the figure shows the pH-induced Cu 2-x Aggregation and deaggregation properties of Se nanozymes, Cu 2-x Se nanozymes aggregate under low pH conditions and depolymerize under high pH conditions; Figure 1 D in is Cu 2-xThe characterization of the hydrated particle size of Se nanozymes under different pH conditions showed that the particle size of the nanoparticles gradually increased with the decrease of pH, indicating that the nanozymes aggregated; Figure 1 E in 1, F in 1 and G in 1 are Cu 2-x FT-IR, TGA and XRD characterizations of Se nanozymes showed that Cu 2-x The successful synthesis of Se nanozymes and the role of BSA and Cu in nanozymes 2-x The composition ratio of Se is ≈11.76:1; Figure 1 H and I in are Cu 2-x XPS characterization of Se nanozymes showed that Cu + and Cu 2+ The ratio is about 3.57:1, which is also the key to the high reactivity of nanozymes; Figure 1 J and K in Cu 2-x The peroxidase-like activity of Se nanozymes in acidic environment is concentration-dependent. Figure 1 L and M in Cu 2-x Se nanozymes have excellent stability in different environmental media.
[0040] Example 2
[0041] (1) Preparation of OHA: 2 g of sodium hyaluronate (HA, Mw = 150-250 kDa) powder was fully dissolved in 200 mL of deionized water, followed by the addition of 1 g of sodium periodate solid. The mixture was stirred at room temperature in the dark for 24 hours, and then 2 mL of ethylene glycol was added to terminate the reaction. The resulting solution was dialyzed against water for 5 days using a dialysis bag with a molecular weight cutoff of 8000-12000 Da, filtered, and freeze-dried for later use to obtain oxidized hyaluronic acid (OHA).
[0042] (2) Synthesize Cu according to Example 1 2-x Se nanozymes.
[0043] (3) Take 20 mg Cu 2-x Se nanozyme, 100 μg glucose oxidase (GOx), 500 mg OHA, and 190.7 mg borax were dissolved in 5 mL of deionized water to obtain a first solution. 1.25 g gelatin and 190.7 mg borax were dissolved in 5 mL of deionized water to obtain a second solution. The first solution and the second solution were thoroughly mixed in a volume ratio of 1:1 to obtain an injectable hydrogel dressing OBG@CG, and the gelation time was about 45 s.
[0044] Comparative Example 1
[0045] (1) OHA was synthesized according to Example 2.
[0046] (2) Take 500 mg OHA and 190.7 mg borax and dissolve them in 5 mL of deionized water to obtain a first solution, take 1.25 g gelatin and 190.7 mg borax and dissolve them in 5 mL of deionized water to obtain a second solution, and mix the first solution and the second solution in a volume ratio of 1:1 to obtain an injectable hydrogel dressing OBG.
[0047] Comparative Example 2
[0048] (1) OHA was synthesized according to Example 2.
[0049] (2) Take 100 μg of glucose oxidase (GOx), 500 mg of OHA, and 190.7 mg of borax and dissolve them in 5 mL of deionized water to obtain a first solution. Take 1.25 g of gelatin and 190.7 mg of borax and dissolve them in 5 mL of deionized water to obtain a second solution. The first solution and the second solution are thoroughly mixed in a volume ratio of 1:1 to obtain an injectable hydrogel dressing OBG@G.
[0050] Comparative Example 3
[0051] (1) Synthesize Cu according to Example 1 2-x Se nanozymes.
[0052] (2) OHA was synthesized according to Example 2.
[0053] (3) Take 20 mg Cu 2-x Se nanozyme, 500 mg OHA, and 190.7 mg borax were dissolved in 5 mL of deionized water to obtain a first solution, 1.25 g gelatin and 190.7 mg borax were dissolved in 5 mL of deionized water to obtain a second solution, and the first solution and the second solution were thoroughly mixed in a volume ratio of 1:1 to obtain the injectable hydrogel dressing OBG@C.
[0054] Application Example 1
[0055] Injectable hydrogel dressing OBG@CG responsively releases GOx and Cu 2-x Se nanozymes and cascade reactions to degrade glucose and produce reactive oxygen species test:
[0056] Methylene blue was used to test the anti-hydroxyl radical ability of the hydrogel. Figure 3 A shows the voids in the hydrogel dressing OBG@CG on Cu 2-x The concentration of Se nanozyme was 0-2 mg mL -1 (Cu in the mixed solution after the first solution and the second solution are mixed 2-xThe concentration range of Se nanozyme decreased with the increase of nanozyme concentration, but when the nanozyme concentration continued to increase to 3 mg mL -1 Instead, it will increase the voids in the gel dressing and make the hydrogel network loose and fragile. Figure 3 B in the figure is the element distribution diagram in OBG@CG, indicating that Cu 2-x Uniform distribution of Se nanozymes in hydrogel. Figure 3 The C in the figure shows the ability of OBG@CG to produce ROS through cascade reaction to oxidize TMB in glucose solutions with different pH values. The lower the pH value, the more obvious the oxidation. Figure 3 D and E in the figure are the gluconic acid and H2O2 produced by OBG@CG in the glucose solution, which trigger the decrease of solution pH value and the change of glucose concentration in the glucose solution. Figure 3 F is the release of Cu by OBG@CG in glucose solution 2-x The properties of Se nanozymes indicate that GOx accelerates Cu 2-x Release of Se nanozymes. Figure 3 G and H in are the degradation rates of different hydrogels in glucose solution and OBG@CG in glucose solution with different pH values.
[0057] Application Example 2
[0058] Hemostatic and angiogenic properties of injectable hydrogel dressing OBG@CG:
[0059] Sodium pentobarbital (2%, w / v, 40 mg kg -1 ) SD rats (male, 6 weeks) were anesthetized. Subsequently, the abdomen of the rats was surgically incised, and the liver was lifted and placed on a pre-weighed filter paper. Afterwards, a longitudinal wound (8 mm in length) was made on the edge of each liver to induce bleeding. 50 μL of hydrogel (OBG, OBG@G, OBG@C, OBG@CG) was injected to fill the wound, and after 60 s, the hemostatic ability of the hydrogel dressing was evaluated by the weight gain of the filter paper that fully absorbed the expelled blood, as shown in Figure 2. Figure 4 The results showed that the liver bleeding of rats with liver injury was immediately controlled after the hydrogel was used to stop bleeding, while the untreated group still had obvious bleeding after 60 seconds.
[0060] HUVECs were plated at 4 × 10 per well. 5 The cells were seeded in a 6-well plate at a density of 100 cells and cultured to a confluence of about 90%. Then, scratches were made with a sterile plastic pipette tip (200 μL) and incubated with fresh culture medium containing different hydrogel extracts (PBS, OBG, OBG@G, OBG@C, and OBG@CG). Cell migration photos were taken under a microscope at specific time points (0 h, 12 h, and 24 h), and the cell migration rate was evaluated using ImageJ software. Figure 5 As shown in A and D. In the Transwell migration assay, the collection concentration was 4×10 5 mL -1 HUVECs were cultured in the upper chamber of the Transwell chamber, and the corresponding hydrogel extracts were added to the lower chamber. After 24 h of incubation, the cells were fixed with 4% paraformaldehyde, stained with crystal violet, washed three times with ethanol, and observed under a microscope. Figure 5 As shown in Figures B and E. In the tube-forming experiment, Matrigel (Corning, USA, 100 μL / well) was injected into a 96-well plate, and HUVECs pretreated with different hydrogel extracts (PBS, OBG, OBG@G, OBG@C, and OBG@CG) were cultured on the Matrigel. After incubation for 2 h, images were taken with an optical microscope, and the length and formation of the tubules in each group were evaluated using ImageJ software, as shown in Figure 1. Figure 5 The expression of HIF-1α and VEGF in HUVECs treated with different hydrogel extracts (PBS, OBG, OBG@G, OBG@C and OBG@CG) is shown in Figure 3C and F. Figure 5 The above results all indicate that OBG@CG has excellent angiogenesis-promoting effect.
[0061] Application Example 3
[0062] Antimicrobial performance testing of injectable hydrogel dressings:
[0063] After different hydrogels (PBS, OBG, OBG@G, OBG@C and OBG@CG) were co-cultured with Staphylococcus aureus E.coli and Escherichia coli S.aureus for 24 hours, the culture solution was evenly spread on the agarose plate medium, and the number of colonies formed was recorded ( Figure 6 AC in the figure). At the same time, the bacteria after co-culture were stained using a live / dead staining kit ( Figure 6 The results show that OBG@G, OBG@C and OBG@CG have strong antibacterial activity. Even with short-term treatment, high-concentration bacteria can still be killed. The morphology of the bacteria treated with hydrogel was observed under a scanning electron microscope after being fixed with glutaraldehyde ( Figure 6 In (D), bacterial cells can be seen adsorbed on the hydrogel surface, and the bacteria shrink and rupture.
[0064] Application Example 4
[0065] Effect of injectable hydrogel dressing in rat infectious diabetic wound model:
[0066] A diabetic rat model was established by intraperitoneal injection of streptozotocin. A circular full-thickness infectious diabetic wound model with a diameter of 8 mm was constructed on the back skin of the rats. Different hydrogels (PBS, OBG, OBG@G, OBG@C and OBG@CG) were used for treatment for 2 weeks, and wound images were collected at different time points (0th, 2nd, 4th, 7th, 10th, and 14th days). Figure 7 A in the figure shows the overall flow chart of using hydrogel dressings to promote the repair of infected diabetic wounds. Figure 7 B in 7 , C in 7 , and F in 7 show the changes in the size of the infected diabetic wound area throughout the treatment process. Figure 7 D and E in the figure are the H&E and Masson staining results of the wound after treatment with hydrogel dressing. Figure 7 The G in the figure is the 7th day of treatment. The wounds of different treatment groups were separated and oscillated, and the eluate was plated and cultured for bacteria to observe the bactericidal effect of the hydrogel dressings in different treatment groups. On the 7th day, the wound size of the OBG@CG treatment group was reduced to 9.13%, and on the 14th day, the wound size was only 0.95%, which was significantly better than other hydrogel treatment groups. H&E and Masson staining also showed that OBG@CG treatment better promoted skin re-epithelialization, collagen deposition, and more orderly arrangement of hair follicles and sebaceous glands.
[0067] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing an injectable hydrogel dressing containing self-assembled activated nanozymes, characterized in that: The preparation method comprises the following steps: (1) Dissolve oxidized hyaluronic acid (OHA) and borax in water and add copper selenide nanozyme Cu 2-x Se and glucose oxidase GOx to obtain a first solution; wherein Cu 2-x x in Se is 0 or 1; (2) dissolving gelatin and borax in water to obtain a second solution; (3) mixing the second solution into the first solution under stirring to form an injectable hydrogel dressing containing self-assembled activated nanozymes; In step (1), the first solution contains Cu 2-x The concentration of Se is 0.1-5 mg mL -1 , GOx concentration was 1-30 μg mL -1 , OHA concentration is 2-10% w / v, borax concentration is 0.01-0.1M; The copper selenide nanozyme Cu 2-x The preparation method of Se comprises: dissolving copper chloride dihydrate and bovine serum albumin in water, adding sodium hydroxide to prepare solution A; dissolving selenium powder and sodium borohydride in water to obtain solution B; adding solution B to solution A to react and obtain copper selenide nanozyme Cu 2-x Se.
2. The preparation of the injectable hydrogel dressing containing self-assembled activated nanozymes according to claim 1, characterized in that: The preparation method of the oxidized hyaluronic acid (OHA) comprises: dissolving sodium hyaluronate in water, adding sodium periodate and reacting at room temperature to obtain the oxidized hyaluronic acid (OHA).
3. The preparation of the injectable hydrogel dressing containing self-assembled activated nanozymes according to claim 1, characterized in that: The molecular weight of the oxidized hyaluronic acid OHA is 8000-12000Da.
4. The preparation of the injectable hydrogel dressing containing self-assembled activated nanozymes according to claim 1, characterized in that: In step (2), the concentration of gelatin in the second solution is 5-30% w / v; the concentration of borax is 0.01-0.1M.
5. An injectable hydrogel dressing containing self-assembled activated nanozymes obtained according to the preparation method according to any one of claims 1 to 4.
6. Use of the hydrogel dressing according to claim 5 in preparing a dressing for diabetic infected wounds.
Citation Information
Patent Citations
Injectable antibacterial hydrogel for promoting healing of diabetes infected wound as well as preparation method and application of injectable antibacterial hydrogel
CN117085170A